2004
DOI: 10.1209/epl/i2003-10302-1
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the coexistence of structural phases and the optical properties of gallium nanoparticles with optical excitation

Abstract: We have observed reversible structural transformations, induced by optical excitation at 1.55 µm, between the β, γ and liquid phases of gallium in self-assembled gallium nanoparticles, with a narrow size distribution around 50 nm, on the tip of an optical fiber. Only a few tens of nanowatts of optical excitation per particle are required to control the transformations, which take the form of a dynamic phase coexistence and are accompanied by substantial changes in the optical properties of the nanoparticle fil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…It is found that there are significant differences in the dielectric function of the various Ga polymorphs, especially in the spectral region below 2.5 eV, with interband transitions in α‐ and β‐Ga and Drude metallic behavior for γ‐Ga and δ‐Ga. Until present, although the different phases have been identified in confined systems (nanostructures), the lack of information on the dielectric dispersion of the different Ga‐phases has hampered the accurate electromagnetic modeling of these Ga nanostructures, pushing experimentalists to approximate the optical constants as linear combinations of the liquid and solid (α‐Ga) phases . Furthermore, we demonstrate that optical constants attributed to α‐Ga in the literature, obtained by supercooling l‐Ga, actually corresponds to the mixture of α‐ with other Ga phases.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is found that there are significant differences in the dielectric function of the various Ga polymorphs, especially in the spectral region below 2.5 eV, with interband transitions in α‐ and β‐Ga and Drude metallic behavior for γ‐Ga and δ‐Ga. Until present, although the different phases have been identified in confined systems (nanostructures), the lack of information on the dielectric dispersion of the different Ga‐phases has hampered the accurate electromagnetic modeling of these Ga nanostructures, pushing experimentalists to approximate the optical constants as linear combinations of the liquid and solid (α‐Ga) phases . Furthermore, we demonstrate that optical constants attributed to α‐Ga in the literature, obtained by supercooling l‐Ga, actually corresponds to the mixture of α‐ with other Ga phases.…”
Section: Discussionsupporting
confidence: 86%
“…Synthesized solid Ga nanoparticles have been reported to present the coexistence of different phases whose structural transformation can be driven by low power (approximately nW) optical excitation . In order to model the plasmonic response of these NPs, and due to the lack of information on the dielectric dispersion profiles of the different Ga phases, the optical properties of the Ga polymorphs were approximated through the linear combination of the dielectric function of l‐ and α‐Ga . Therefore, we have simulated the plasmonic response of NPs with different geometries made of the different Ga phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of electromagnetic and transport properties of granular, fractal media and metamaterials is also a welldeveloped science and has attracted much attention in the area of condensed matter physics. However, within the cuboids in order to obtain the required range of ε r , μ r and conductivity, important phenomena such as Coulomb blockade (CB), kinetic inductance and the effects of quantum coherence will be taken into consideration by our colleagues in the Physics Department at Loughborough University [33][34][35].…”
Section: Interactions On a Atomic And Quantum Levelmentioning
confidence: 99%
“…3a). [7,11] and are related to the nature of the phase transition process in nanoparticles. In bulk solids, phase transitions are characterized by a discontinuous (irreversible) rearrangement of the crystalline lattice at a specific temperature.…”
mentioning
confidence: 99%